Efektivitas Pengelolaan Dana Desa dalam Upaya Peningkatan Pembangunan di Desa Sifaoroasi Kecamatan Huruna Kabupaten Nias Selatan - Yosua Kevin Rezeki; Nina Angelia; Evi Yunita Kurniaty (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2022)
One of the identification problems in managing village funds in the village of Sifaoroasi, Huruna district, South Nias district, which still cannot be said to be fully effective, especially in the development of the village.  This study uses qualitative methods as data analysis.  The data sources in this study were the head of the Sifaoroasi village, the head of planning affairs, village officials, the head of the hamlet and the community of the Sifaoroasi village.  Data were collected based on data collection techniques, namely observation, interviews, documentation and data triangulation.  The results show that the management of village funds in an effort to increase development in the village of Sifaoroasi, Huruna sub-district, South Nias district is still not effective, this can be seen from the perspective of village development that has not been fully realized effectively in 2020. Thus it can be seen from the theory.  used in this research is the clarity of the objectives to be achieved, the clarity of strategic achievement of objectives, the process of analysis and problem formulation, sound policies, proper planning, proper programming, the availability of facilities and infrastructure for monitoring and control systems are still not effective and are not effective.  according to what the community wants in the village.  The factors that influence the management of village funds in Sifaoroasi village, Huruna district, South Nias district are human resources, facilities and infrastructure as well as transportation tools that support the development of the village.